Indonesian Economic Structure: An Analysis of Temporal Leontief Inverse - Firmansyah Firmansyah; Shanty Oktavilia (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
This study aims to analyze the Indonesia economic structure with employing the temporal Leontief inverse which was developed by Sonis and Hewings (1998) on 1975-2005 Indonesia’s input-output tables. In the first stage, this study investigates how the manufacturing industries in driving the Indonesian economy during structural changes. In the second stage, this study examines the structural changes of the manufacturing industries, which can explain the trends in individual industry balance in the context of the economic system. Based on the analysis, this study can trace how each year’s change contributes to the total impact in gross output change.